Faktor-Faktor yang Mempengaruhi Earnings Response Coeficient pada Perusahaan yang Terdaftar di Bursa Efek Jakarta - Sri Mulyani; Nur Fadjrih Asyik; Andayani Andayani (Jurnal Akuntansi dan Auditing Indonesia, 2007)
The objective of this study is to examine factors affect earnings response coefficient consist of earnings persistence, capital structure, systematic risk (beta), earnings growth, and firm size (Scott, 2000). The study added one variable, that is audit quality. Teoh and Wong (1993) argue that audit quality is positively associated with client’s quality of earnings and the earnings response coefficient.Samples used in this study are 255 firms listed in the Jakarta Stock Exchange (JSE) from 2001-2005. The study tested hypothesis by using multiple regression analysis models. The results of study show that all of the factors (earnings persistence, capital structure, systematic risk (beta), earnings growth, and firm size) influence earnings response coefficients, exception audit quality is not statistically significant influence earnings response coefficients. Keywords: earnings response coefficient, audit quality, earnings quality